Intensification of dimethyaminoethoxyethanol on CO2 absorption in ionic liquid of amino acid. (August 2016) - Zhang, Feng; Gao, Kai-Xuan; Meng, Yu-Ning; Qi, Min; Geng, Jiao; Wu, You-Ting; Zhang, Zhi-Bing
Graphical abstract: Highlights: Anhydrous solution of AAIL and DMEE is proposed as new absorbent of CO2 . Low viscosity, phase splitting and proton transfer between AAIL and DMEE enable the fast and large uptake of CO2 . The new absorbent can be regenerated and recycled with low energy consumption. Abstract: New anhydrous CO2 absorbents were prepared with: tetramethylammonium glycinate ([N1111 ][Gly]), a task specific ionic liquid (TSIL), and dimethyaminoethoxyethanol (DMEE). The absorption of CO2 was studied over a wide range of IL concentration (5–60 wt%), temperature (298–318 K) and CO2 pressure (0–300 kPa). The addition of DMEE was found to be able to greatly accelerate the CO2 absorption as well as increase CO2 loading in [N1111 ][Gly] since it reduced the fluid viscosity as well as acted as a proton acceptor. CO2 reacted with IL and precipitated and can be removed from the system and subsequently regenerated by heat. The regeneration efficiencies of the solutions at 353 K are higher than 97% and decrease very little in the next absorption circles. The anhydrous CO2 absorbents showed an advantage of a higher regeneration efficiency at relatively lower temperature and less energy consumption than aqueous solutions of alkanolamines.